Patient delivered partner therapy for chlamydia infection is used by some general practitioners, but more support is needed to increase uptake: findings from a mixed-methods study. (30th June 2021) - Goller, Jane L; Coombe, Jacqueline; Bittleston, Helen; Bourne, Christopher; Bateson, Deborah; Vaisey, Alaina; Tomnay, Jane; O'Donnell, Heather; Garret, Cameryn; Estcourt, Claudia S; Temple-Smith, Meredith; Hocking, Jane S
Abstract : Objectives: Patient-delivered partner therapy (PDPT) describes the giving of a prescription or antibiotics by an index case with chlamydia to their sexual partners. PDPT has been associated with higher numbers of partners receiving treatment. In Australia, general practitioners (GPs) previously expressed negative views about PDPT. Health authority guidance for PDPT has since been provided in some areas. We investigated recent use and perceptions of PDPT for chlamydia among GPs in Australia. Methods: In 2019, we conducted an online survey comprising multiple-choice and open-ended questions to investigate GPs' chlamydia management practices, including PDPT. Logistic regression identified factors associated with ever offering PDPT. A directed content analysis of free-text data explored GPs' perceptions towards PDPT. Results: The survey received responses from 323 GPs; 85.8% (n=277) answered PDPT-focused questions, providing 628 free-text comments. Over half (53.4%) reported never offering PDPT, while 36.5% sometimes and 10.1% often offered PDPT. GPs more likely to offer PDPT were aged ≥55 years (adjusted OR (AOR) 2.9, 95% CI 1.4 to 5.8), worked in non-metropolitan areas (AOR 2.5, 95% CI 1.5 to 4.4) and jurisdictions with health authority PDPT guidance (AOR 2.3, 95% CI 1.4 to 3.9). Qualitative data demonstrated that many GPs recognised PDPT's potential to treat harder to engage partners but expressed hesitancy to offer PDPT because they considered partners attending for care as best practice. GPs emphasised a case-by-case approach that considered patient and partner circumstances to determine PDPT suitability. To alleviate medicolegal concerns, many GPs indicated a need for professional and health authority guidance that PDPT is permissible. They also desired practical resources to support its use. Conclusion: GPs appear to accept the place of PDPT as targeted to those who may otherwise not access testing or treatment. Availability of health authority guidance appears to have supported some GPs to incorporate PDPT into their practice.